Conceptual approaches to the development of rural areas, taking into account the European experience - A. I. Kostyaev (Аграрная наука Евро-Северо-Востока, 2018)
The normative legal documents in force in Russia (concept, strategy, program) for sustainable development of rural areas are imperfect. They do not take into account the European experience of rural development. The concept and the program expire in 2020. When developing these documents for a new period, one should take into account the historical experience of the European Union (EU). The establishment of a scientific paradigm and conceptual approaches to the development of rural areas in Russia, with due regard to the European experience in the formulation of the author, is new. The aim of the study is to substantiate conceptual approaches to the development of rural areas of Russia, in view of the fundamental principles of building a system for managing rural development in the EU countries. A scientific assessment of conceptual approaches to the development of rural areas in the EU is given. Since the early 1990s, the process of substitution of the exogenous-branch approach for the more progressive - endogenous-territorial and the formation of elements of the new - neo-endogenous approach - has been taking place in the EU countries. The most acceptable for the conditions of modern Russia is the endogenous-territorial approach. Its main features: the use of local natural, human, cultural and other resources; local initiative and entrepreneurial attitude, the creation of partnerships; multifunctionality of agriculture and diversification of the local economy; formation of social capital at the local level, development of "rural networks"; strengthening the institutional and infrastructural capacity of rural areas, overcoming their isolation from the outside world. The realizing of such an approach will require a complicated and painstaking work to create institutions for development and self-development, including resource potential in the development of rural areas. The "bottom-up" movement with financial, informational and institutional support "top-down" can fundamentally change the socio-economic situation in rural areas. At the same time, institutional prerequisites will be created for the subsequent transition to a neo-endogenous approach in the development of rural areas.